Young People’s Response to Parental Neurological Disorder: A Structured Review - Hartman L; Jenkinson C; Morley D (Dove Medical Press, 2020)
Lilian Hartman,1 Crispin Jenkinson,2 David Morley2 1Lincoln College, University of Oxford, Oxford OX1 3DR, UK; 2Nuffield Department of Population Health, University of Oxford, Oxford OX3 7LF, UKCorrespondence: David Morley Tel +44 1865 289432Email david.morley@ndph.ox.ac.ukIntroduction: A significant paucity of literature exists relating to the impact on children of parental neurological disorder, with the exception of multiple sclerosis. The wider literature in this field (parental cancer, depression, alcoholism, HIV/AIDS) exhibits the many potential challenges young people might experience during serious parental illness. Given this, a literature review of parental neurological disorder is long overdue.Methods: This review is structured around the World Health Organisation (WHO) classification of neurological disorders. The WHO identifies 10 common neurological disorders; dementia, epilepsy, headache, multiple sclerosis, neuroinfections, neurological disorders associated with malnutrition, pain associated with neurological disorders, Parkinson’s disease, stroke, and traumatic brain injury. A comprehensive search of the MEDLINE database was performed using key terms for each of the 10 conditions. Results for each condition were divided in to “negative”, “positive and/or neutral” and “other” child responses.Results: The search yielded a total of 6247 titles, of which 184 underwent a full-text assessment. Sixty-five met all eligibility criteria and were thus included in the review. A number of negative issues emerged across parental conditions including the prevalence of child mood disorders, parent-child role reversal, children’s need for information on the parental condition, the importance of family cohesion, the negative effect of parental psychopathology and differences between male and female children. A limited number of positive outcomes were evident in a minority of parental conditions. Outcomes measured and methodologies employed were highly heterogeneous.Conclusion: Children generally respond negatively to parental neurological disorder. Responses varied between neurological disorders, suggesting the need for parental disease-specific guidance and clinical management where required.Keywords: parental illness, neurological disorder, young people, children, parent, World Health Organisation, outcomes, review